Carbon ceramic brake pad material and method for manufacturing the same
Patent Information
- Application Number
- CN202610383903.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-03-26
AI Technical Summary
然而,上述短纤模压-液相渗硅路线在实际应用中面临两个尚未得到有效解决的技术难题:第一,碳纤维与基体界面结合强度不足的问题
(1)本发明提供的碳陶刹车片材料,通过对碳纤维进行特定的化学预处理和溶胶-凝胶碳热还原涂层改性,在碳纤维表面原位构建TiC/ZrC双相纳米复合涂层,再结合中间相沥青焦、硼改性酚醛树脂、鳞片石墨与纳米B4C多组元基体配方,经热压成型、碳化、反应熔渗及硅除杂热处理制得碳陶刹车片材料;所得材料中碳纤维完整性得到有效保护,纤维增强效率提升;在反应熔渗阶段,液态硅与碳化坯体中的游离碳原位反应生成SiC,同时纳米B4C与液态硅反应原位生成B掺杂SiC相,最终基体由游离碳化物、SiC及B掺杂SiC共同构成,具有较好的力学性能和摩擦学性能,满足碳陶刹车片在高温、高载荷服役条件下对材料强度、耐磨性和摩擦稳定性的综合要求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of brake pad material technology, specifically relating to a carbon ceramic brake pad material and its preparation method. Background Technology
[0002] Braking systems are the core components for safe braking in automobiles, high-speed trains, and aircraft. Their working principle involves converting kinetic energy into heat energy through the relative motion of the friction surfaces, dissipating enormous braking energy in a very short time. Therefore, brake materials not only need to possess a stable and suitable coefficient of friction, but also must simultaneously meet the requirements of high mechanical strength, excellent wear resistance, good high-temperature stability, and reliable resistance to thermal shock.
[0003] Traditional brake materials mainly fall into three categories: cast iron, powder metallurgy, and resin-based friction materials. Cast iron brake materials have a high density, and under high-speed, heavy-load conditions, their heavy weight and poor thermal conductivity make them prone to thermal fade and deformation, leading to decreased braking stability. Powder metallurgy brake materials, in emergency braking scenarios exceeding 380 km / h, can reach friction interface temperatures of 900-1000℃, approaching their service limits and failing to meet the braking requirements of higher speed levels. Resin-based friction materials have even more limited heat resistance and high-temperature strength, resulting in rapid wear under continuous high-temperature braking conditions. These three types of traditional brake materials are all ill-suited to the development requirements of high-performance braking systems in terms of density, high-temperature performance, and service life.
[0004] Carbon fiber reinforced silicon carbide (C / C-SiC) composites, also known as carbon-ceramic composites, are a new generation of advanced braking materials developed based on C / C materials. Compared to C / C materials, carbon-ceramic materials introduce a SiC ceramic phase, offering the following significant advantages: lower density, approximately one-quarter that of cast iron brake materials; higher and more stable coefficient of friction, with minimal difference between wet and dry states, overcoming the fundamental defect of wet friction decay in C / C materials; better wear resistance, with a service life more than five times that of traditional metal brake materials; and superior oxidation resistance compared to C / C materials, significantly improving reliability during high-temperature service.
[0005] The main methods for preparing carbon-ceramic materials include chemical vapor infiltration (CVI), precursor impregnation pyrolysis (PIP), and reactive infiltration / sulfurization (RMI / LSI). In the reactive infiltration method for preparing carbon-ceramic materials, using chopped carbon fibers as reinforcement combined with a molding process (i.e., short fiber molding-carbonization-liquid phase silica infiltration route) is an effective way to reduce production costs and shorten the preparation cycle. However, the aforementioned short fiber molding-liquid phase silica infiltration route faces two unresolved technical challenges in practical applications: First, the insufficient interfacial bonding strength between carbon fibers and the matrix. After high-temperature carbonization, chopped carbon fibers exhibit high chemical inertness, with very few surface-active functional groups and low surface energy, making it difficult to form effective chemical bonds with both organic (phenolic resin) and inorganic (SiC) matrices, resulting in low fiber-matrix interfacial bonding strength. During braking, carbon fibers are easily pulled out of the matrix or undergo interfacial debonding, causing a decrease in the material's mechanical properties (especially flexural strength and interlaminar shear strength) and tribological properties, thus shortening the material's service life. Second, there is the issue of erosion of the carbon fiber matrix by liquid silicon during the liquid-phase silicon infiltration process. During the reactive melting infiltration (liquid-phase silicon infiltration) stage, liquid silicon (melting point 1414℃) infiltrates the preform under capillary force. While reacting with the carbon matrix to form SiC, it inevitably comes into direct contact with the carbon fibers, which act as reinforcement, and undergoes an erosive reaction. This results in a reduction in carbon fiber diameter, surface damage, and a significant decrease in fiber strength. This problem is particularly prominent in chopped carbon fiber reinforced systems, as the chopped carbon fibers are directly dispersed in the matrix, resulting in a large contact area with the liquid silicon and a more severe degree of erosion. Ultimately, this makes it difficult for the material's mechanical properties to reach the expected level, severely restricting further improvements in the overall performance of short-fiber molded carbon ceramic brake pads.
[0006] Therefore, how to effectively improve the interfacial bonding strength between carbon fibers and the matrix in the short fiber molding-liquid phase silicon infiltration route, while protecting the carbon fibers from liquid silicon erosion, is a core technical problem that urgently needs to be solved in this field, and it is also the key to developing high-performance carbon fiber reinforced carbon ceramic brake pad materials. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a carbon ceramic brake pad material and its preparation method.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: Carbon fiber is added to nitric acid solution for oxidation pretreatment. After treatment, it is filtered, washed and dried. The resulting solid product is added to tannic acid aqueous solution, the pH is adjusted to 8-9, and it is stirred and adsorbed. After adsorption, it is filtered and dried to obtain pretreated carbon fiber. S2. Modification of carbon fiber: Add pretreated carbon fiber to composite sol, ultrasonically impregnate, then take it out and dry it. Repeat the impregnation-drying operation 2-4 times, then perform pre-sintering. After the pre-sintering is completed, transfer it to a vacuum furnace for calcination to obtain modified carbon fiber. S3. Hot pressing: Modified carbon fiber, mesophase pitch coke, boron-modified phenolic resin, hexamethylenetetramine, flake graphite, and nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is loaded into a mold for hot pressing to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen to carry out carbonization. After carbonization is completed, it is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. After the treatment is completed, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment, cooled with the furnace, and polished to obtain the carbon ceramic brake pad material.
[0009] Preferably, the mass concentration of the nitric acid solution in step S1 is 20-25%, the temperature of the impregnation treatment is 50-80℃, and the time is 2-4h.
[0010] Preferably, the mass concentration of the tannic acid solution in step S1 is 1-2%, the stirring and adsorption temperature is 20-30℃, and the time is 60-90 min.
[0011] Preferably, the preparation method of the composite sol in step S2 is as follows: 20-40g of tetrabutyl titanate and 10-15g of zirconium oxychloride are added to 100-150g of anhydrous ethanol, followed by 0.6-1g of acetylacetone and 10-20g of furfuryl alcohol. After stirring evenly, 5-10g of deionized water is slowly added dropwise. The mixture is stirred at 20-30℃ for 2-4 hours and allowed to stand for aging for 24-48 hours to obtain the composite sol.
[0012] Preferably, in step S2, the ultrasonic impregnation temperature is 25-40℃, the time is 20-30 min, and the ultrasonic power is 100-200W; the pre-sintering process is: heating to 300-400℃ at a rate of 3-5℃ / min in an atmospheric environment and holding for 1-2 hours; the calcination process is: evacuating to a vacuum level of no more than 5×10⁻⁶ ppm in the furnace. -1 Pa, heated to 1500-1550℃ at a heating rate of 5-8℃ / min, and held at that temperature for 1.5-2.5h.
[0013] Preferably, the mass ratio of modified carbon fiber, mesophase pitch coke, boron-modified phenolic resin, hexamethylenetetramine, flake graphite, and nano boron carbide powder in step S3 is 40-45:35-42:10-15:5-8:5-10:3-6. The hot pressing process is as follows: apply pressure of 15-20t throughout the process, raise the temperature to 70-90℃ at a rate of 3-8℃ / h, hold for 2-4h, raise the temperature to 130-150℃ at a rate of 4-6℃ / h, hold for 1-2h, raise the temperature to 190-205℃ at a rate of 2-4℃ / h, and hold for 2-3h.
[0014] This invention uses boron-modified phenolic resin instead of ordinary phenolic resin as the binder and curing agent in the hot pressing stage. The BO bonds of the boron-modified phenolic resin participate in the cross-linking between benzene rings, resulting in a higher residual carbon rate after curing compared to ordinary phenolic resin. The higher residual carbon rate increases the carbide content in the carbonized preform, providing more carbon sources that can react with liquid silicon to generate SiC for subsequent reaction infiltration. This is beneficial for increasing the volume fraction of SiC in the matrix and the overall hardness of the material, reducing the risk of thermal stress caused by temperature gradients inside the preform during curing, and reducing the probability of surface cracks in the preform.
[0015] Preferably, the carbonization process in step S4 is as follows: the temperature is increased from room temperature to 300-350°C at a rate of 10-15°C / h, and then increased to 900-1000°C at a rate of 15-20°C / h, and held at that temperature for 4-6 hours.
[0016] The carbonization process of this invention adopts a two-stage heating strategy: in the stage from room temperature to 300-350℃, the temperature is increased at a relatively slow rate of 10-15℃ / h, so that the organic components (boron-modified phenolic resin and volatiles in mesophase pitch coke) slowly pyrolyze in the low-temperature zone, and the volatile small molecule gases can escape fully and steadily, avoiding cracks caused by a sudden increase in internal pressure of the green body due to local rapid gas generation; in the stage above 300-350℃, the temperature is appropriately increased to 15-20℃ / h, taking into account both production efficiency and green body integrity, ensuring that the organic matrix is fully carbonized, and providing appropriate open porosity and silicon diffusion channels for subsequent silicon diffusion.
[0017] Preferably, the silicon infiltration process in step S5 is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 4-6 kPa, the temperature is raised to 1700-1850℃ at a rate of 5-10℃ / min, and held for 3-6 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.2-1.5 times the mass of the carbonized preform.
[0018] Nano-B4C powder was introduced into the matrix formulation, and reactive melting was carried out under a slightly negative pressure nitrogen atmosphere (4-6 kPa). During the silicon infiltration process, the nano-B4C reacted with liquid silicon, and B atoms dissolved into the SiC lattice, forming a B-doped SiC phase in situ in the matrix. B doping can reduce the SiC grain boundary energy, refine the SiC grains, and improve the fracture toughness of the matrix. At the same time, the B-doped SiC phase has a lower surface energy than pure SiC, which helps to reduce the friction coefficient decay rate of the material in humid environments and improve wet braking stability. The slightly negative pressure nitrogen atmosphere allows a small number of N atoms to dissolve in the SiC unit cell, further inhibiting the excessive growth of SiC grains during the high-temperature silicon infiltration stage, synergistically refining the matrix grain structure and improving the bending strength of the material.
[0019] This invention employs a reactive melting infiltration method (liquid-phase silicon infiltration) as a densification means. During the silicon infiltration stage, liquid silicon infiltrates into the open pore network of the carbonized preform under the drive of capillary force, and reacts in situ with the free carbon in the preform (from the residual carbon of boron-modified phenolic resin carbonization, the residual carbon of mesophase pitch coke carbonization, and flake graphite). The generated SiC fills the pores and together with the carbon fibers and residual carbon, forms a dense composite matrix. At the same time, nano-B4C powder reacts with liquid silicon in situ to generate B-doped SiC phase, which further fills the pores of the matrix, giving the material excellent density and mechanical load-bearing capacity.
[0020] Preferably, the heat treatment process in step S6 is as follows: under vacuum conditions, the temperature is raised to 1600-1700℃ at a rate of 180-220℃ / h and held for 3-6h.
[0021] This invention also protects a carbon-ceramic brake pad material prepared by the method described above.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The carbon-ceramic brake pad material provided by the present invention is obtained by subjecting carbon fiber to specific chemical pretreatment and sol-gel carbothermal reduction coating modification, constructing TiC / ZrC dual-phase nanocomposite coating on the surface of carbon fiber in situ, and then combining the mesophase pitch coke, boron-modified phenolic resin, flake graphite and nano B4C multi-component matrix formulation, and then obtaining the carbon-ceramic brake pad material by hot pressing, carbonization, reaction melting and infiltration and silicon impurity removal heat treatment; the integrity of carbon fiber in the obtained material is effectively protected and the fiber reinforcement efficiency is improved; in the reaction melting stage, liquid silicon reacts with free carbon in the carbonized blank to generate SiC in situ, and at the same time, nano B4C reacts with liquid silicon to generate B-doped SiC phase in situ. Finally, the matrix is composed of free carbide, SiC and B-doped SiC, which has good mechanical properties and tribological properties, and meets the comprehensive requirements of carbon-ceramic brake pads for material strength, wear resistance and friction stability under high temperature and high load service conditions.
[0023] (2) The carbon-ceramic brake pad material provided by the present invention uses a two-step method of nitric acid oxidation pretreatment and tannic acid modification to activate the carbon fiber surface during the pretreatment of carbon fiber. Nitric acid oxidation introduces oxygen-containing functional groups such as carboxyl and hydroxyl groups on the carbon fiber surface, making it change from chemically inert to hydrophilic, and providing the active binding sites required for subsequent tannic acid anchoring. Under weakly alkaline conditions (pH=8-9), tannic acid forms a uniform enriched layer on the carbon fiber surface through multiple interactions such as hydrogen bonding, π-π stacking and oxidative self-polymerization. The enriched layer is rich in pyrogallol hydroxyl groups. It can coordinate and hydrogen bond with TiO2 and ZrO2 in the subsequent composite sol, significantly improving the wettability, single loading, and coating uniformity of the composite sol on the carbon fiber surface. At the same time, the tannic acid layer is carbonized in situ during the subsequent high-temperature calcination process, forming a carbonaceous transition layer between the carbon fiber and the TiC / ZrC coating. This helps to alleviate the mismatch in the coefficients of thermal expansion between the two, and through the chemical affinity between the carbonaceous layer and TiC and ZrC, it improves the bonding strength between the coating and the carbon fiber matrix, and inhibits the cracking and peeling of the coating during thermal cycling.
[0024] (3) The carbon-ceramic brake pad material provided by the present invention uses furfuryl alcohol as a polymeric carbon source in the composite sol system when modifying pretreated carbon fibers. It coexists with TiO2 / ZrO2 precursors in the same sol system. Because furfuryl alcohol molecules and TiO2 / ZrO2 nanoparticles generated by hydrolysis and condensation in the sol are uniformly mixed in the liquid phase, the two are in close contact. In the pre-sintering stage, furfuryl alcohol undergoes thermal cross-linking and solidification, retaining the above-mentioned mixed state in solid form. In the subsequent vacuum calcination stage (900-1100℃), furfuryl alcohol carbonizes to form highly active carbon, which is in close contact with the surrounding TiO2 / ZrO2 particles and undergoes a carbothermic reduction reaction, generating a TiC / ZrC biphase nanocomposite coating in situ on the carbon fiber surface. Compared with the traditional carbothermic method that requires the addition of external carbon source powder, In this reduction route, the carbon source and oxide precursor are in uniform contact, effectively shortening the solid-phase diffusion distance of the carbothermic reduction reaction, resulting in higher reaction efficiency and high purity of the obtained TiC and ZrC phases, as well as a dense and uniform coating. The TiC / ZrC biphase nanocomposite coating generated in situ on the carbon fiber surface plays an effective physicochemical shielding role for the carbon fiber during the reaction melting and infiltration stage. TiC and ZrC are thermodynamically stable in liquid silicon and do not react significantly with liquid silicon, effectively preventing liquid silicon from penetrating into and corroding the carbon fiber body through capillary force, thereby preserving the original mechanical properties of the carbon fiber and allowing it to fully exert its reinforcing and toughening role in the SiC matrix. Compared with carbon fibers without coating protection, carbon fibers protected by TiC / ZrC coating show improved overall bending strength and fracture toughness after silicon infiltration. Detailed Implementation
[0025] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] Unless otherwise specified, all chemical reagents and materials in this invention are purchased from the market or synthesized from raw materials purchased from the market.
[0027] The boron-modified phenolic resin was purchased from Xuzhou Yihuiyang New Material Co., Ltd.; the carbon fiber has a length of 3-6 mm and a diameter of 7-12 μm; the true density of the mesophase pitch coke is not less than 2.0 g / cm³. 3 The ash content is not higher than 0.5 wt%, and the particle size is 10-75 μm; the particle size of the flake graphite is 10-50 μm; and the particle size of the nano boron carbide powder is 50-200 nm.
[0028] Example 1
[0029] A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: 500g of carbon fiber was added to 2L of 25% nitric acid solution and oxidized at 60℃ for 3h. After treatment, the carbon fiber was filtered, washed and dried. The resulting solid product was added to 3L of 1.5% tannic acid aqueous solution and the pH was adjusted to 8.5. The mixture was stirred and adsorbed at 25℃ for 80min. After adsorption, the carbon fiber was filtered and dried to obtain pretreated carbon fiber. S2. Modification of carbon fiber: 500g of pretreated carbon fiber was added to 5L of composite sol and ultrasonically impregnated at 30℃ and 150W for 25min. Then, it was removed and dried at 100℃ for 2h. This impregnation-drying process was repeated three times. Subsequently, the temperature was increased to 350℃ at a rate of 4℃ / min in atmospheric environment for pre-sintering for 1.5h. After pre-sintering, it was transferred to a vacuum furnace and evacuated until the vacuum level inside the furnace did not exceed 5×10⁻⁶. -1 Pa was heated to 1500℃ at a heating rate of 6℃ / min and calcined for 2 hours to obtain modified carbon fibers. S3. Hot pressing: 430g of modified carbon fiber, 380g of mesophase pitch coke, 130g of boron-modified phenolic resin, 60g of hexamethylenetetramine, 80g of flake graphite, and 50g of nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is placed into a mold for hot pressing. The hot pressing process is as follows: apply a pressure of 18t throughout the process, raise the temperature to 80℃ at a rate of 5℃ / h, hold for 3h, raise the temperature to 140℃ at a rate of 5℃ / h, hold for 1.5h, raise the temperature to 200℃ at a rate of 3℃ / h, and hold for 2.5h to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen for carbonization. The carbonization process is as follows: the temperature is raised from room temperature to 330°C at a rate of 12°C / h, then raised to 950°C at a rate of 18°C / h, and held for 5 hours. After carbonization, the billet is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. The silicon infiltration treatment process is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 5 kPa, the temperature is raised to 1800℃ at a rate of 7℃ / min, and held for 5 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.4 times the mass of the carbide preform. After the treatment, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment. The heat treatment process is as follows: under vacuum conditions, the temperature is raised to 1650℃ at a rate of 200℃ / h, held for 5h, cooled with the furnace, and then polished to obtain the carbon ceramic brake pad material.
[0030] The preparation method of the composite sol in step S2 is as follows: 30g tetrabutyl titanate and 13g zirconium oxychloride are added to 130g anhydrous ethanol, followed by 0.8g acetylacetone and 15g furfuryl alcohol. After stirring evenly, 8g deionized water is slowly added dropwise. The mixture is stirred at 25°C for 3 hours and allowed to stand for 36 hours to obtain the composite sol.
[0031] Example 2
[0032] A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: 500g of carbon fiber was added to 2L of 20% nitric acid solution and oxidized at 80℃ for 2h. After treatment, the carbon fiber was filtered, washed and dried. The solid product was added to 3L of 1% tannic acid aqueous solution and the pH was adjusted to 8. The carbon fiber was stirred and adsorbed at 20℃ for 90min. After adsorption, the carbon fiber was filtered and dried to obtain pretreated carbon fiber. S2. Modification of carbon fiber: 500g of pretreated carbon fiber was added to 5L of composite sol and ultrasonically impregnated at 20°C and 100W for 0min. Then, it was removed and dried at 100°C for 2h. This impregnation-drying process was repeated 3 times. Subsequently, the temperature was increased to 300°C at a rate of 3°C / min in an atmospheric environment for pre-sintering for 2h. After pre-sintering, it was transferred to a vacuum furnace and evacuated until the vacuum level inside the furnace did not exceed 5×10⁻⁶. -1 Pa was heated to 1500℃ at a heating rate of 5℃ / min and calcined for 1.5h to obtain modified carbon fibers. S3. Hot pressing: 400g of modified carbon fiber, 350g of mesophase pitch coke, 100g of boron-modified phenolic resin, 50g of hexamethylenetetramine, 50g of flake graphite, and 30g of nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is placed into a mold for hot pressing. The hot pressing process is as follows: a pressure of 15t is applied throughout the process, the temperature is raised to 70℃ at a rate of 3℃ / h and held for 4h, the temperature is raised to 130℃ at a rate of 4℃ / h and held for 2h, and the temperature is raised to 190℃ at a rate of 2℃ / h and held for 3h to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen for carbonization. The carbonization process is as follows: the temperature is raised from room temperature to 300℃ at a rate of 10℃ / h, then raised to 900℃ at a rate of 15℃ / h, and held for 6 hours. After carbonization is completed, the billet is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. The silicon infiltration treatment process is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 4 kPa, the temperature is raised to 1700℃ at a rate of 5℃ / min, and held for 6 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.2 times the mass of the carbide preform. After the treatment, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment. The heat treatment process is as follows: under vacuum conditions, the temperature is raised to 1600℃ at a rate of 180℃ / h, held for 6h, cooled with the furnace, and then polished to obtain the carbon ceramic brake pad material.
[0033] The preparation method of the composite sol in step S2 is as follows: 20g tetrabutyl titanate and 10g zirconium oxychloride are added to 100g anhydrous ethanol, followed by 0.6g acetylacetone and 10g furfuryl alcohol. After stirring evenly, 5g deionized water is slowly added dropwise. The mixture is stirred at 20°C for 4 hours and allowed to stand for 48 hours to obtain the composite sol.
[0034] Example 3
[0035] A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: 500g of carbon fiber was added to 2L of 25% nitric acid solution and oxidized at 50℃ for 4h. After treatment, the carbon fiber was filtered, washed and dried. The solid product was added to 3L of 2% tannic acid aqueous solution and the pH was adjusted to 9. The carbon fiber was stirred and adsorbed at 30℃ for 60min. After adsorption, the carbon fiber was filtered and dried to obtain pretreated carbon fiber. S2. Modification of carbon fiber: 500g of pretreated carbon fiber was added to 5L of composite sol and ultrasonically impregnated at 40℃ and 200W for 20min. Then, it was removed and dried at 100℃ for 2h. This impregnation-drying process was repeated three times. Subsequently, the temperature was increased to 400℃ at a rate of 4℃ / min in an atmospheric environment for pre-sintering for 1h. After pre-sintering, the carbon fiber was transferred to a vacuum furnace and evacuated until the vacuum level inside the furnace did not exceed 5×10⁻⁶. -1 Pa was heated to 1500℃ at a heating rate of 8℃ / min and calcined for 2.5h to obtain modified carbon fibers; S3. Hot pressing: 450g of modified carbon fiber, 420g of mesophase pitch coke, 150g of boron-modified phenolic resin, 80g of hexamethylenetetramine, 100g of flake graphite, and 60g of nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is placed into a mold for hot pressing. The hot pressing process is as follows: a pressure of 20t is applied throughout the process, the temperature is raised to 90℃ at a rate of 8℃ / h and held for 2 hours, the temperature is raised to 150℃ at a rate of 6℃ / h and held for 1 hour, and the temperature is raised to 205℃ at a rate of 4℃ / h and held for 2 hours to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen for carbonization. The carbonization process is as follows: the temperature is raised from room temperature to 350℃ at a rate of 15℃ / h, then raised to 1000℃ at a rate of 20℃ / h, and held for 4 hours. After carbonization is completed, the billet is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. The silicon infiltration treatment process is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 6 kPa, the temperature is raised to 1850℃ at a rate of 10℃ / min, and held for 3 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.5 times the mass of the carbide preform. After the treatment, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment. The heat treatment process is as follows: under vacuum conditions, the temperature is raised to 1700℃ at a rate of 220℃ / h, held for 3h, cooled with the furnace, and then polished to obtain the carbon ceramic brake pad material.
[0036] The preparation method of the composite sol in step S2 is as follows: 40g tetrabutyl titanate and 15g zirconium oxychloride are added to 150g anhydrous ethanol, followed by 1g acetylacetone and 20g furfuryl alcohol. After stirring evenly, 10g deionized water is slowly added dropwise. The mixture is stirred at 30°C for 2 hours and allowed to stand for 24 hours to obtain the composite sol.
[0037] Comparative Example 1
[0038] A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: Add 500g of carbon fiber to 2L of 25% nitric acid solution and oxidize at 60℃ for 3h. After treatment, filter, wash and dry to obtain pretreated carbon fiber. S2. Modification of carbon fiber: 500g of pretreated carbon fiber was added to 5L of composite sol and ultrasonically impregnated at 30℃ and 150W for 25min. Then, it was removed and dried at 100℃ for 2h. This impregnation-drying process was repeated three times. Subsequently, the temperature was increased to 350℃ at a rate of 4℃ / min in atmospheric environment for pre-sintering for 1.5h. After pre-sintering, it was transferred to a vacuum furnace and evacuated until the vacuum level inside the furnace did not exceed 5×10⁻⁶. -1 Pa was heated to 1500℃ at a heating rate of 6℃ / min and calcined for 2 hours to obtain modified carbon fibers. S3. Hot pressing: 430g of modified carbon fiber, 380g of mesophase pitch coke, 130g of boron-modified phenolic resin, 60g of hexamethylenetetramine, 80g of flake graphite, and 50g of nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is placed into a mold for hot pressing. The hot pressing process is as follows: apply a pressure of 18t throughout the process, raise the temperature to 80℃ at a rate of 5℃ / h, hold for 3h, raise the temperature to 140℃ at a rate of 5℃ / h, hold for 1.5h, raise the temperature to 200℃ at a rate of 3℃ / h, and hold for 2.5h to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen for carbonization. The carbonization process is as follows: the temperature is raised from room temperature to 330°C at a rate of 12°C / h, then raised to 950°C at a rate of 18°C / h, and held for 5 hours. After carbonization, the billet is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. The silicon infiltration treatment process is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 5 kPa, the temperature is raised to 1800℃ at a rate of 7℃ / min, and held for 5 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.4 times the mass of the carbide preform. After the treatment, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment. The heat treatment process is as follows: under vacuum conditions, the temperature is raised to 1650℃ at a rate of 200℃ / h, held for 5h, cooled with the furnace, and then polished to obtain the carbon ceramic brake pad material.
[0039] The preparation method of the composite sol in step S2 is as follows: 30g tetrabutyl titanate and 13g zirconium oxychloride are added to 130g anhydrous ethanol, followed by 0.8g acetylacetone and 15g furfuryl alcohol. After stirring evenly, 8g deionized water is slowly added dropwise. The mixture is stirred at 25°C for 3 hours and allowed to stand for 36 hours to obtain the composite sol.
[0040] Compared with Example 1, this comparative example did not involve tannic acid treatment during carbon fiber pretreatment.
[0041] Comparative Example 2
[0042] A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: 500g of carbon fiber was added to 2L of 25% nitric acid solution and oxidized at 60℃ for 3h. After treatment, the carbon fiber was filtered, washed and dried. The resulting solid product was added to 3L of 1.5% tannic acid aqueous solution and the pH was adjusted to 8.5. The mixture was stirred and adsorbed at 25℃ for 80min. After adsorption, the carbon fiber was filtered and dried to obtain pretreated carbon fiber. S2. Hot pressing: 430g of pretreated carbon fiber, 380g of mesophase pitch coke, 130g of boron-modified phenolic resin, 60g of hexamethylenetetramine, 80g of flake graphite, and 50g of nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is placed into a mold for hot pressing. The hot pressing process is as follows: apply a pressure of 18t throughout the process, raise the temperature to 80℃ at a rate of 5℃ / h, hold for 3h, raise the temperature to 140℃ at a rate of 5℃ / h, hold for 1.5h, raise the temperature to 200℃ at a rate of 3℃ / h, and hold for 2.5h to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen for carbonization. The carbonization process is as follows: the temperature is raised from room temperature to 330°C at a rate of 12°C / h, then raised to 950°C at a rate of 18°C / h, and held for 5 hours. After carbonization, the billet is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. The silicon infiltration treatment process is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 5 kPa, the temperature is raised to 1800℃ at a rate of 7℃ / min, and held for 5 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.4 times the mass of the carbide preform. After the treatment, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment. The heat treatment process is as follows: under vacuum conditions, the temperature is raised to 1650℃ at a rate of 200℃ / h, held for 5h, cooled with the furnace, and then polished to obtain the carbon ceramic brake pad material.
[0043] Compared with Example 1, this comparative example did not modify the pretreated carbon fiber, i.e., step S2 was omitted.
[0044] Comparative Example 3
[0045] A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: 500g of carbon fiber was added to 2L of 25% nitric acid solution and oxidized at 60℃ for 3h. After treatment, the carbon fiber was filtered, washed and dried. The resulting solid product was added to 3L of 1.5% tannic acid aqueous solution and the pH was adjusted to 8.5. The mixture was stirred and adsorbed at 25℃ for 80min. After adsorption, the carbon fiber was filtered and dried to obtain pretreated carbon fiber. S2. Modification of carbon fiber: 500g of pretreated carbon fiber was added to 5L of composite sol and ultrasonically impregnated at 30℃ and 150W for 25min. Then, it was removed and dried at 100℃ for 2h. This impregnation-drying process was repeated three times. Subsequently, the temperature was increased to 350℃ at a rate of 4℃ / min in atmospheric environment for pre-sintering for 1.5h. After pre-sintering, it was transferred to a vacuum furnace and evacuated until the vacuum level inside the furnace did not exceed 5×10⁻⁶. -1 Pa was heated to 1500℃ at a heating rate of 6℃ / min and calcined for 2 hours to obtain modified carbon fibers. S3. Hot pressing: 430g of modified carbon fiber, 380g of mesophase pitch coke, 130g of boron-modified phenolic resin, 60g of hexamethylenetetramine, 80g of flake graphite, and 50g of nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is placed into a mold for hot pressing. The hot pressing process is as follows: apply a pressure of 18t throughout the process, raise the temperature to 80℃ at a rate of 5℃ / h, hold for 3h, raise the temperature to 140℃ at a rate of 5℃ / h, hold for 1.5h, raise the temperature to 200℃ at a rate of 3℃ / h, and hold for 2.5h to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen for carbonization. The carbonization process is as follows: the temperature is raised from room temperature to 330°C at a rate of 12°C / h, then raised to 950°C at a rate of 18°C / h, and held for 5 hours. After carbonization, the billet is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. The silicon infiltration treatment process is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 5 kPa, the temperature is raised to 1800℃ at a rate of 7℃ / min, and held for 5 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.4 times the mass of the carbide preform. After the treatment, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment. The heat treatment process is as follows: under vacuum conditions, the temperature is raised to 1650℃ at a rate of 200℃ / h, held for 5h, cooled with the furnace, and then polished to obtain the carbon ceramic brake pad material.
[0046] The preparation method of the composite sol in step S2 is as follows: 30g tetrabutyl titanate is added to 130g anhydrous ethanol, followed by 0.8g acetylacetone and 15g furfuryl alcohol. After stirring evenly, 8g deionized water is slowly added dropwise. The mixture is stirred at 25°C for 3 hours and allowed to stand for 36 hours to obtain the composite sol.
[0047] Compared to Example 1, zirconium oxychloride was not introduced into the composite sol of this comparative example.
[0048] Comparative Example 4
[0049] A method for preparing a carbon-ceramic brake pad material includes the following steps: S1. Pretreatment of carbon fiber: 500g of carbon fiber was added to 2L of 25% nitric acid solution and oxidized at 60℃ for 3h. After treatment, the carbon fiber was filtered, washed and dried. The resulting solid product was added to 3L of 1.5% tannic acid aqueous solution and the pH was adjusted to 8.5. The mixture was stirred and adsorbed at 25℃ for 80min. After adsorption, the carbon fiber was filtered and dried to obtain pretreated carbon fiber. S2. Modification of carbon fiber: 500g of pretreated carbon fiber was added to 5L of composite sol and ultrasonically impregnated at 30℃ and 150W for 25min. Then, it was removed and dried at 100℃ for 2h. This impregnation-drying process was repeated three times. Subsequently, the temperature was increased to 350℃ at a rate of 4℃ / min in atmospheric environment for pre-sintering for 1.5h. After pre-sintering, it was transferred to a vacuum furnace and evacuated until the vacuum level inside the furnace did not exceed 5×10⁻⁶. -1 Pa was heated to 1500℃ at a heating rate of 6℃ / min and calcined for 2 hours to obtain modified carbon fibers. S3. Hot pressing: 430g of modified carbon fiber, 380g of mesophase pitch coke, 130g of boron-modified phenolic resin, 60g of hexamethylenetetramine, 80g of flake graphite, and 50g of nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is placed into a mold for hot pressing. The hot pressing process is as follows: apply a pressure of 18t throughout the process, raise the temperature to 80℃ at a rate of 5℃ / h, hold for 3h, raise the temperature to 140℃ at a rate of 5℃ / h, hold for 1.5h, raise the temperature to 200℃ at a rate of 3℃ / h, and hold for 2.5h to obtain a hot-pressed blank. S4. Carbonization: The hot-pressed billet is placed in a carbonization furnace, vacuumed and filled with nitrogen for carbonization. The carbonization process is as follows: the temperature is raised from room temperature to 330°C at a rate of 12°C / h, then raised to 950°C at a rate of 18°C / h, and held for 5 hours. After carbonization, the billet is cooled to room temperature with the furnace to obtain a carbonized billet. S5. Reactive infiltration: The carbide preform and silicon powder are placed in a reactive infiltration furnace for silicon infiltration treatment. The silicon infiltration treatment process is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 5 kPa, the temperature is raised to 1800℃ at a rate of 7℃ / min, and held for 5 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.4 times the mass of the carbide preform. After the treatment, a silicon-infiltrated preform is obtained. S6. Silicon impurity removal heat treatment: The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment. The heat treatment process is as follows: under vacuum conditions, the temperature is raised to 1650℃ at a rate of 200℃ / h, held for 5h, cooled with the furnace, and then polished to obtain the carbon ceramic brake pad material.
[0050] The preparation method of the composite sol in step S2 is as follows: 30g tetrabutyl titanate and 13g zirconium oxychloride are added to 130g anhydrous ethanol, followed by 0.8g acetylacetone. After stirring evenly, 8g deionized water is slowly added dropwise. The mixture is stirred at 25°C for 3 hours and allowed to stand for 36 hours to obtain the composite sol.
[0051] Compared to Example 1, furfuryl alcohol was not added to the composite sol in this comparative example.
[0052] The carbon-ceramic brake pad materials prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests. The apparent porosity was tested according to standard GB / T 25995-2010 "Test Method for Density and Apparent Porosity of Fine Ceramics"; the flexural strength was tested according to standard GB / T 6569-2006 "Test Method for Flexural Strength of Fine Ceramics" using the three-point bending method, with a span of 30 mm, a loading rate of 0.5 mm / min, and sample sizes of 3 mm × 4 mm × 36 mm. At least 5 samples were tested in each group, and the average value was taken; the fracture toughness was tested according to standard GB / T 23806-2025 "Test Method for Fracture Toughness of Fine Ceramics - Single-Sided Precracked Beam (SEPB) Method"; the dry friction coefficient, wear rate, peak-to-valley ratio of the friction curve, and wet braking performance attenuation rate were tested in an MM-1000 friction testing machine. The test parameters were as follows: moment of inertia: 0.37 kg·m. 2 Linear velocity: 25 m / s; braking pressure: 0.8 MPa; number of braking cycles: 10 (the friction surface adhesion rate needs to be ≥80% before formal testing); mating material: carbon-ceramic composite material prepared in the same batch; the dry friction coefficient test result is the average of 10 braking data; wear rate (μm / surface·cycle) = thickness difference of sample before and after braking (μm) / number of braking cycles, take the cumulative thickness change of 10 braking cycles divided by 10; the peak-to-valley ratio of the friction curve is the ratio of the maximum value to the minimum value of the friction coefficient curve of 10 braking cycles, that is: peak-to-valley ratio = μ max / μ min During the wet test, deionized water was continuously sprayed onto the friction surface at a rate of 20 mL / min. After a stable spraying time of 1 min, the braking test was performed. The wet friction coefficient was taken as the average of three braking tests. The wet braking performance attenuation rate was calculated using the following formula: Attenuation rate (%) = (dry μ - wet μ) / dry μ × 100%. The test results are shown in Table 1 below.
[0053] Table 1
[0054] As can be seen from Table 1 above, the carbon-ceramic brake pad material prepared by this invention has good mechanical and tribological properties, meeting the comprehensive requirements of carbon-ceramic brake pads for material strength, wear resistance and frictional stability under high temperature and high load service conditions.
[0055] The above description is a further detailed explanation of the present invention in conjunction with specific implementation examples. It should not be considered that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention, and all such deductions or substitutions should be considered to fall within the protection scope of the present invention.
[0056] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-ceramic brake pad material, characterized in that, Includes the following steps: S1. Add carbon fiber to nitric acid solution for oxidation pretreatment. After treatment, filter, wash and dry. Add the obtained solid product to tannic acid aqueous solution, adjust the pH to 8-9, stir and adsorb. After adsorption, filter and dry to obtain pretreated carbon fiber. S2. Add the pretreated carbon fiber to the composite sol, ultrasonically impregnate it, then take it out and dry it. Repeat the impregnation-drying operation 2-4 times, then perform pre-sintering. After the pre-sintering is completed, transfer it to a vacuum furnace for calcination to obtain modified carbon fiber. S3. Modified carbon fiber, mesophase pitch coke, boron-modified phenolic resin, hexamethylenetetramine, flake graphite, and nano boron carbide powder are added to a mixer and mixed evenly to obtain a mixture. Then, the mixture is loaded into a mold for hot pressing to obtain a hot-pressed blank. S4. Place the hot-pressed billet in a carbonization furnace, evacuate and fill with nitrogen to carry out carbonization. After carbonization is completed, cool the billet to room temperature with the furnace to obtain a carbonized billet. S5. Place the carbide preform and silicon powder in a reaction melting furnace for silicon infiltration treatment. After the treatment is completed, a silicon-infiltrated preform is obtained. S6. The silicon-diffused preform is placed in a vacuum heat treatment furnace for heat treatment, cooled with the furnace, and polished to obtain the carbon-ceramic brake pad material. The preparation method of the composite sol in step S2 is as follows: 20-40g of tetrabutyl titanate and 10-15g of zirconium oxychloride are added to 100-150g of anhydrous ethanol, followed by 0.6-1g of acetylacetone and 10-20g of furfuryl alcohol. After stirring evenly, 5-10g of deionized water is slowly added dropwise. The mixture is stirred at 20-30℃ for 2-4 hours and allowed to stand for aging for 24-48 hours to obtain the composite sol.
2. The preparation method according to claim 1, characterized in that, In step S1, the mass concentration of the nitric acid solution is 20-25%, and the temperature of the oxidation pretreatment is 50-80℃, with a time of 2-4 hours.
3. The preparation method according to claim 1, characterized in that, The mass concentration of the tannic acid solution in step S1 is 1-2%, and the stirring and adsorption temperature is 20-30℃, and the time is 60-90 min.
4. The preparation method according to claim 1, characterized in that, In step S2, the ultrasonic impregnation temperature is 25-40℃, the time is 20-30 min, and the ultrasonic power is 100-200W; the pre-sintering process is: heating to 300-400℃ at a rate of 3-5℃ / min in an atmospheric environment and holding for 1-2 hours; the calcination process is: evacuating to a vacuum level of no more than 5×10⁻⁶ ppm in the furnace. -1 Pa, heated to 1500-1550℃ at a heating rate of 5-8℃ / min, and held at that temperature for 1.5-2.5h.
5. The preparation method according to claim 1, characterized in that, In step S3, the mass ratio of modified carbon fiber, mesophase pitch coke, boron-modified phenolic resin, hexamethylenetetramine, flake graphite, and nano boron carbide powder is 40-45:35-42:10-15:5-8:5-10:3-6. The hot pressing process is as follows: apply pressure of 15-20t throughout the process, raise the temperature to 70-90℃ at a rate of 3-8℃ / h, hold for 2-4h, raise the temperature to 130-150℃ at a rate of 4-6℃ / h, hold for 1-2h, raise the temperature to 190-205℃ at a rate of 2-4℃ / h, and hold for 2-3h.
6. The preparation method according to claim 1, characterized in that, The carbonization process described in step S4 is as follows: the temperature is increased from room temperature to 300-350℃ at a rate of 10-15℃ / h, and then increased to 900-1000℃ at a rate of 15-20℃ / h, and held at that temperature for 4-6 hours.
7. The preparation method according to claim 1, characterized in that, The silicon infiltration process described in step S5 is as follows: the nitrogen pressure in the furnace is maintained at a slight negative pressure of 4-6 kPa, the temperature is raised to 1700-1850℃ at a rate of 5-10℃ / min, and held for 3-6 hours; the purity of the silicon powder used is not less than 99%, the particle size is not more than 400 mesh, and the amount of silicon powder used is 1.2-1.5 times the mass of the carbonized preform.
8. The preparation method according to claim 1, characterized in that, The heat treatment process described in step S6 is as follows: under vacuum conditions, the temperature is raised to 1600-1700℃ at a rate of 180-220℃ / h and held for 3-6 hours.
9. A carbon-ceramic brake pad material prepared by the method according to any one of claims 1-8.
Citation Information
Patent Citations
Low-cost carbon-ceramic brake material and preparation method thereof
CN117024152A
Method for carrying out surface modification on carbon fibers by coupling tannic acid with nano graphene oxide
CN118621579A